Neofusicoccum luteum as a pathogen on Tejocote (Crataegus mexicana) - ADESEMOYE, Anthony; MAYORQUIN, Joey; ESKALEN, Akif (Phytopathologia Mediterranea, 2012)
Tejocote (Crataegus mexicana), a small pome crab-apple-like fruit, is becoming economically important in California with increasing production, so consideration of diseases that hinder the yield is important. Diseased trees of tejocote were observed in four orchards of Riverside and San Diego Counties of California. Ten symptomatic/asymptomatic samples were studied from each of the orchards. Five most frequently isolated fungi were identified on the basis of morphological characters and sequence data of the internal transcribed spacer ITS1-5.8S-ITS2 and partial β-tubulin gene. Three isolates were identified as Neofusicoccum luteum and two as Phomopsis sp. Pathogenicity tests were conducted by inoculating detached shoots of healthy tejocote trees. Significant lesions were observed on all shoots inoculated with the three N. luteum isolates (designated UCR1190, UCR1191, and UCR1192), but not on the shoots inoculated with other isolates or the non-inoculated controls. Results indicated that all three N. luteum isolates are aggressive pathogens on tejocote. This pathosystem should be further studied with a goal of designing appropriate disease management strategies.